2016
DOI: 10.1021/jacs.6b07010
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High Figure of Merit in Phase-Separated Polycrystalline Sn1–xPbxSe

Abstract: Solid-state thermoelectric technology, interconverting heat to electrical energy, offers a promising solution for relaxing global energy problems. A high dimensionless figure of merit ZT is desirable for high-efficiency thermoelectric power generation. To date, thermoelectric materials research has focused on increasing the material's ZT. Here we first fabricated phase-separated SnPbSe materials by hydrothermal synthesis. We demonstrate that the simultaneous optimization of the power factor and significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
193
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(207 citation statements)
references
References 34 publications
12
193
2
Order By: Relevance
“…Because of high electrical and low thermal conductivities at x=0.2, the highest ZT value is 0.75 at ~790 K, while that at x=0 is only 0.27. Although this ZT value is still lower than those of state-of-the-art mid temperature TE materials, like elemental tellurium (ZT=~1.0 at 700 K), 39 PbTe-(ZT=2.5 at 923 K) 40 and SnSe-based (ZT=1.7 at 873 K) alloys, 41,42 it stands among the tops for ternary Cu-Sn-S sulfides at the corresponding temperatures.…”
Section: Te Performancementioning
confidence: 77%
“…Because of high electrical and low thermal conductivities at x=0.2, the highest ZT value is 0.75 at ~790 K, while that at x=0 is only 0.27. Although this ZT value is still lower than those of state-of-the-art mid temperature TE materials, like elemental tellurium (ZT=~1.0 at 700 K), 39 PbTe-(ZT=2.5 at 923 K) 40 and SnSe-based (ZT=1.7 at 873 K) alloys, 41,42 it stands among the tops for ternary Cu-Sn-S sulfides at the corresponding temperatures.…”
Section: Te Performancementioning
confidence: 77%
“…i) TEM image of SnSe mesoscale grains and boundaries with EBSD image inset showing the orientation difference between grains and bar chart inset showing grain size distribution. Reproduced with permission 23. Copyright 2016, American Chemical Society.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Compared with SnSe single crystals, polycrystalline SnSe has interfaces such as grain boundaries in their structures, which can be treated as a “treasury” because the interfaces are the places that high‐density point defects and dislocations (mainly edge dislocations) prior to exist, thus play significant roles in producing massive strain fields around interfaces to strengthen the phonon scattering and in turn reduce κ l . Figure 16i shows a typical TEM image of SnSe mesoscale grains, fabricated via a typical hydrothermal route 23. The grain boundaries can be clearly seen with a high density.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…That is, enhancement of charge transport capability (power factor PF = S σ 2 ) and slowing the heat propagation will lead to the promotion of ZT value. It is widely reported that charge transport properties can be improved by tuning the carrier density or mobility through element doping, alloys, defect engineering et al However, thermal conductivity could be reduced by reinforcing the scattering of phonons, which consumes the vibrational energy between adjacent atoms through chemical bonding and plays an important role in the heat propagation, with the strategies of nanostructuring, all‐scale hierarchical architecturing, composite engineering et al…”
Section: Introductionmentioning
confidence: 99%